2013
DOI: 10.4049/jimmunol.1301450
|View full text |Cite
|
Sign up to set email alerts
|

Acute Plasmodium chabaudi Infection Dampens Humoral Responses to a Secondary T-Dependent Antigen but Enhances Responses to a Secondary T-Independent Antigen

Abstract: High rates of coinfection occur in malaria endemic regions, leading to more severe disease outcomes. Understanding how coinfecting pathogens influence the immune system is important in the development of treatment strategies that reduce morbidity and mortality. Using the Plasmodium chabaudi mouse model of malaria and immunization with model Ags that are either T-dependent (4-hydroxy-3-nitrophenyl [NP]-OVA) or T-independent (NP-Ficoll), we analyzed the effects of acute malaria on the development of humoral immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…In models of autoimmunity, sepsis, or chronic inflammation, aberrant expansion of short-lived ASCs has been shown to disrupt the establishment and retention of a LLPC population (5358). We found that accumulation of BM ASCs was defective in mice challenged with Δ srrAB 14 days earlier (Supplemental Figure 3E), and by 14 days post-challenge, no bacteria were found in the kidneys of mice from any group (data not shown) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In models of autoimmunity, sepsis, or chronic inflammation, aberrant expansion of short-lived ASCs has been shown to disrupt the establishment and retention of a LLPC population (5358). We found that accumulation of BM ASCs was defective in mice challenged with Δ srrAB 14 days earlier (Supplemental Figure 3E), and by 14 days post-challenge, no bacteria were found in the kidneys of mice from any group (data not shown) .…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that the expansion of short-lived extrafollicular ASCs occurs at the expense of GC formation (53, 61). This could reduce the pool of ASCs selected for long-term survival in the BM since post-GC PCs likely have a selective advantage once they reach the BM (62).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data obtained in this work provide information that allows us to partially explain there is a delayed GC response and a significant reduction of the humoral response to Tdependent antigens 35 . Interestingly, we also observed that PD-L1 neg plasmablast functioned as an enhancers of T cell response ( Fig.4a and 4c) since in infected-chimera mice the frequency of PD-1 + IFN -+ TNF + -producing T cells was higher than in mice without plasmablast.…”
Section: Pd-l1 High Expression On Antibody-secreting Cells Was Previomentioning
confidence: 75%
“…It is considered a genetically attenuated strain that is generated through many cycles within a mosquito vector, the intermediate host [ 15 , 16 ], which can quickly evolve into a more virulent form when in contact with the definitive host [ 17 ]. Studies have shown that there is an increase in the infectious process accompanied by the production of interferon gamma (IFNγ), which facilitates a response to TLR agonists, followed by an increase in serum IgG titers of cured mice [ 18 , 19 ]. Thus, the immune system provides malarial resistance in the infected animal through different mechanisms, which ensures a more efficient healing response [ 20 ].…”
Section: Introductionmentioning
confidence: 99%